Outsourcing malaysia federal tax audit: The stakeholders' views - Norsiah, Ahmad; Zakiah, Muhammadun Mohammed; Takiah, Mohd Iskandar (2014)
This study investigates the feasibility of outsourcing tax audit work in Malaysian tax system to enhance administration efficiency, to curb tax evasion and abusive avoidance, and to improve revenue collection without introducing a new tax. The current tax audit, carried out by internal auditors of Inland Revenue Board of Malaysia, could only be performed on a small numbers of taxpayers due to high administrative cost in terms of audit cost and cost to employ and train more audit personnel. Nevertheless, without tax audit, tax non-compliance activity could not be curbed and government would be at high risk of losing its revenue. One of the possible ways to increase audit work is through strategic outsourcing. However, decision to outsource tax work should be critically examined because outsourcing of tax audit is a policy that could potentially affect every taxpayer. This paper discusses the views of the stakeholders (tax authorities, the taxpayers and tax agents) on the value of tax audit outsourcing. Using a mixed method approach, this study finds contradicting opinions on the idea of implementing external tax audit in Malaysia. While the tax authorities are hesitant to the idea, the companies as tax payers and the tax agents show favorable responds to the implementation of outsourced tax audit in Malaysia.